2007
DOI: 10.1002/eji.200636782
|View full text |Cite
|
Sign up to set email alerts
|

Robust CD4+ and CD8+ T cell responses to SIV using mRNA‐transfected DC expressing autologous viral Ag

Abstract: A potentially powerful strategy for therapeutic HIV vaccination is the use of DC transfected with mRNA encoding autologous viral Ag, as epitopes presented by transfected DC would exactly reflect those expressed by infected cells in the individual. Using human and rhesus macaque monocyte-derived DC, we show that nucleofection is a superior method for mRNA transfection, resulting in high-level protein expression and DC maturation. DC transfected with SIV gag isolated from an infected monkey stimulated robust Ag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
5
32
0
Order By: Relevance
“…Recently, we (47,48,61) and others (9,15,22,28,40,54,57) have shown that transfection with mRNA is more effective than mRNA lipofection, peptide pulsing, or viral transduction to generate primary (65) and memory (57) responses. Furthermore, we demonstrated that DC from treatment-naïve HIV-1-seropositive subjects can efficiently be transfected with HIV gag and env mRNA, derived either from consensus subtype B or autologous viral or proviral HIV, and that these DC readily trigger autologous CD4 ϩ and CD8 ϩ T cells to release IFN-␥ and IL-2 in a short-term ex vivo enzyme-linked immunospot (ELISPOT) assay (60).…”
mentioning
confidence: 99%
“…Recently, we (47,48,61) and others (9,15,22,28,40,54,57) have shown that transfection with mRNA is more effective than mRNA lipofection, peptide pulsing, or viral transduction to generate primary (65) and memory (57) responses. Furthermore, we demonstrated that DC from treatment-naïve HIV-1-seropositive subjects can efficiently be transfected with HIV gag and env mRNA, derived either from consensus subtype B or autologous viral or proviral HIV, and that these DC readily trigger autologous CD4 ϩ and CD8 ϩ T cells to release IFN-␥ and IL-2 in a short-term ex vivo enzyme-linked immunospot (ELISPOT) assay (60).…”
mentioning
confidence: 99%
“…Generation of the pSP73/GFP/A64 and pSP73/SIVmac239Gag/A64 plasmids and in vitro transcription of mRNA were performed as described previously (33). pSP73/SIVmac239Gag/A64 encodes a wild-type, non-codon-optimized Gag sequence isolated from a rhesus macaque 2 weeks postinfection with the SIVmac239 SIV isolate (33).…”
Section: Methodsmentioning
confidence: 99%
“…Generation of the pSP73/GFP/A64 and pSP73/SIVmac239Gag/A64 plasmids and in vitro transcription of mRNA were performed as described previously (33). pSP73/SIVmac239Gag/A64 encodes a wild-type, non-codon-optimized Gag sequence isolated from a rhesus macaque 2 weeks postinfection with the SIVmac239 SIV isolate (33). pSP73/SIVmac239Gag/ A64 was used as a template for the amplification of Gag by PCR using the following forward and reverse primers, respectively: pGagN1F, 5ЈGCGCTCGAGGCCAC CATGGGCGTGAG3Ј; and pGagN1R, 5ЈCGCGCGGCCGCTTACTTGCCCA ACTGCATGTAG 3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations